Agustín Basave Fernández del Valle, La sinrazón metafísica del ateísmo. Prólogo de Stanislaus Ladusans S. I. Universidad Regiomontana-Publicaciones Paulinas S. A. México 1995. 252 páginas - García Losada, Matilde Isabel (1996)
Fil: García Losada, Matilde Isabel. Investigadora Independiente; Argentina